The Effect of Night Extension Splinting Following Surgical Release of Dupuytren’s Contracture - Collis, Julie (Auckland University of Technology, 2012)
The application of splints following surgical release of Dupuytren’s contracture has long been recommended for maintaining finger extension. Questions exist regarding the efficacy and potential detrimental effects of this treatment approach. The literature pertaining to the effects of splints on finger range of motion and hand function following surgery was systematically reviewed. A search of electronic databases was conducted and a quality assessment was undertaken using the Downs and Black Quality Index. A comparison was made with findings from a 2008 systematic literature review. The results of the review suggested that the traditional practice of providing night extension splints was not effective and highlighted the need for further studies. A single centre randomised trial was conducted to investigate the effect of night extension splinting on finger range of motion and hand function in the three months following surgical release of Dupuytren’s contracture. Fifty six patients (males n=45, females n=11) between the ages of 48 and 86 were included in the study. Participants were randomised to receive a night extension splint plus hand therapy (n= 26) or hand therapy alone (n=30). The primary outcome was total active extension (TAE) of the little finger in degrees. Secondary outcomes were total active flexion (TAF) of the fingers in degrees, active distal palmar crease (ADPC) in cm, grip strength in kg, self-reported hand function using the Disabilities of the Arm shoulder and Hand (DASH) questionnaire (1-100 scale) and patient satisfaction. Primary analysis was by intention to treat. There were no statistically significant differences between the no splint and splint groups for any of the outcomes measured. When compared with the splint group the no splint group showed adjusted mean differences of little finger TAE -9.8 (95%CI -20.19 to 0.59, p=0.07), little finger TAF 12.7 (95%CI -1.8 to 27.2, p= 0.08) and ADPC -0.21 (95%CI -0.74 to 0.32, p=0.44). Equally there were no statistical differences for DASH -1.1 (95%CI -5.41 to 3.21, p=0.59), left hand grip strength 2.6 (95%CI -1.52 to 6.72, p=0.22) or right hand grip strength 2.5 (95%CI -0.64 to 5.64, p=0.10). A secondary per protocol analysis was conducted which also showed no statistically significant differences. Although statistical significance was not reached there was a consistent trend across all outcomes in favour of not splinting. The data were also evaluated to identify how well finger extension was maintained overall between the first postoperative measure and three months postoperatively. Of all 40 little fingers 62.5% had the same or better TAE (13⁰ unadjusted mean improvement) and 37.5% had lost TAE (32⁰ unadjusted mean loss) over this period. It was concluded that night extension splinting in combination with standard hand therapy has no greater effect on maintaining finger extension than hand therapy alone in the three months following surgical release of Dupuytren’s contracture. The trend towards poorer outcomes in the splinted group also suggested that splinting is not a benign therapy. The results of this trial indicate that the practice of providing every patient with a night extension splint following surgical release of Dupuytren’s contracture may no longer be justified.
Keywords: Splint; Dupuytren's contracture; Occupational therapy; Hand therapy; Physiotherapy; RCT